TAKDIR DAN KEBEBASAN MENURUT FETHULLAH GÜLEN - Anang Haderi (Jurnal Theologia, 2014)
Abstract:Destiny and free will is one of issues in Islamic theology which is still discussed by Moslem theologian up to now. This discussion has yielded some streams with its argumentation respectively. Included who intense to discuss this issue is muḥammad Fethullah Gülen. At a glance, he offers to explain the issue in his own way without following one of the streams. He introduces some key terms, like Imām Mubīn, Kitāb Mubīn, Lauḥ Maḥfūẓ, Formal or Theoretical Destiny, actual destiny. Terms are Gülen’s exclusive. The article will elaborate the explaination of Gülen relating to the destiny and free will. The purpose is to map what is he follows the streams or he has interpretation in himself. For this reason, I will spread out briefly views of theologian before, i.e. these streams of Mu’tazili, al-Asy’arite, Matūridite Samarkand dan Matūridite Bukhārā. By this way it will be seen clearly where is the position of Gülen and what is contribution of his thinking. Abstrak: takdir dan kebebasan adalah isu teologi Islam yang masih diperbincangkan oleh para teolog hingga sekarang. Perdebatan ini telah melahirkan berbagai aliran dengan pen¬dapat¬nya masing-masing. Termasuk yang juga intens mem¬bahas isu ini adalah Muḥammad Fethullah Gülen. Sekilas, ia berusaha menjelaskan isu ini dengan caranya sendiri tanpa mengikuti salah satu aliran tersebut. Ia mengenalkan be¬berapa istilah kunci, seperti Imām Mubīn, Kitāb Mubīn, Lauḥ Maḥfūẓ, takdir formal, takdir teoritis, dan takdir aktual. Istilah-istilah ini merupakan khas Gülen. Tulisan ini akan mengelaborasi penjelasan Gülen mengenai takdir dan ke¬bebas¬an tersebut. Tujuannya adalah memetakan apakah ia mengikuti aliran-aliran teologi yang sudah ada ataukah ia mempunyai pemaknaan sendiri ter¬hadap persoalan ini. Untuk alasan ini, penulis akan me¬mapar¬kan secara singkat pendapat para teolog sebelumnya, yakni aliran-aliran Mu’tazi¬lah, al-Asy’ariyah, Mātūridiyah Samarkand dan Mātūridiyah Bukhārā. Dengan cara ini akan terlihat dengan jelas di mana¬kah posisi Gülen dan apa kontribusi dari pemikirannya itu. Keywords: Imām Mubīn, Kitāb Mubīn, Lauḥ Maḥfūẓ, takdir formal, takdir aktual.